Comparison of mechanical and wearing properties between LM13 matrix and Stir cast LM13/B4C/Gr hybrid composites of various composition - Faisal, M.H.; Prabagaran, S.; Vishnu, T.S. (International Journal of Engineering and Technology, 2017)
Aluminium/graphite composites are the need of modern times for addressing the fuel saving issues. The graphite in such composites act as solid lubricant and it reduce external fuel requirements. But such composites are having degraded mechanical properties due toÂ theÂ graphite content in composite. In order to solve the negative effect of graphite on mechanical properties ofÂ LM13/Gr self-lubricating composite this study was conducted to find outÂ the mechanical properties ofÂ LM13/B4C/Gr Metal Matrix Composites. Boron carbideÂ was selectedÂ as reinforcement because of its better reinforcement properties compared to alumina and silicon carbide. The properties of the hybrid composites were compared with theÂ LM13/Gr self-lubricating composite to study the enhancement in mechanical properties thatÂ has been causedÂ by the boron carbide particles. Using computerized universal testing machine andÂ rock-wellÂ hardness tester mechanical properties such as hardness and tensile strengthÂ were tested. Pin on disk testing machineÂ was usedÂ to analyse the wear behavior. The test results indicates that by raising weight % of boron carbide particles in theÂ LM13, tensile strength and hardness of the hybrid compositesÂ was increasedÂ compared to self-lubricating composite accompanied by betterÂ tribologicalÂ properties.